2018
DOI: 10.1371/journal.pone.0200907
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Eye Movement test and dyslexic children: A pilot study with eye movement recordings

Abstract: The goal of this study is to explore eye movement recordings during the Developmental Eye Movement (DEM) test in dyslexic and non-dyslexic children. Thirteen children with dyslexia, 13 non-dyslexic chronological age- and IQ-matched children and 13 non-dyslexic reading age- and IQ-matched children were examined. Test C of the DEM test was performed with and without eye movement recordings (eye tracker by SuriCog). The results of the three groups were compared. Children with dyslexia and non-dyslexic children of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 27 publications
7
37
0
Order By: Relevance
“…Both vertical and horizontal DEM times strongly related to the visual processing speed measured in the SA test as well as the eye fixation durations measured in the DEM. These findings agree with the results of Ayton et al 10 and Moiroud et al 20 for the horizontal DEM, and extend the results to the vertical DEM. Additionally, we found that faster performance on the horizontal DEM coincided with fewer, but typically larger saccades.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Both vertical and horizontal DEM times strongly related to the visual processing speed measured in the SA test as well as the eye fixation durations measured in the DEM. These findings agree with the results of Ayton et al 10 and Moiroud et al 20 for the horizontal DEM, and extend the results to the vertical DEM. Additionally, we found that faster performance on the horizontal DEM coincided with fewer, but typically larger saccades.…”
Section: Discussionsupporting
confidence: 92%
“…3 a bottom; r = 0.39, p = 0.018), but the median amplitude of return sweep saccades was not age-dependent (r = 0.21, p = 0.23). Based on previous research 10 , 20 , we expected a decrease in fixation durations with improved performance. The median fixation duration indeed decreased with improving DEM times but only during the number identification epochs (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, DEM outcomes obtained in the CG differed significantly from those obtained in the OAG and LDG. As in previous studies [43], significantly longer times for reading sheet C was observed in the group with specific learning disorders. Furthermore, higher DEM pattern values and ratios, as well as a lower percentile for horizontal time, were found in the LDG compared to the CG.…”
Section: Discussionsupporting
confidence: 86%